Modified and secure adaptive clustering approach for autonomic wireless sensor network with minimum radio energy - Mandal, Sandip; Sushil, Rama (International Journal of Engineering and Technology, 2018)
Wireless sensor networks are a trend of the past few years, and they involve deploying a large number of small nodes. The rapid advancement of wireless technology has enabled the development of small, powerful and expensive sensor nodes, which are capable of sensing, computation and wireless communication. The sensor networks can be used in environmental changes and report, health, military etc. Sensor nodes are limited in power, computational capacities and memory. For these reasons, researchers are currently focusing on the design of power-aware protocols and algorithms for sensor networks. Clustering based schemes are believed to be the most energy efficient routing protocols for wireless sensor networks. Clustering is grouping of similar objects or the process of finding a natural association among some specific objects or data. Clustering leverages the advantages of small transmit distances for most of nodes, requiring only a few nodes to transmit far distances to the sink/base station.The main objective is to develop an energy efficient routing protocol based on clustering along with the reduction in energy consumption so that it improves network lifetime. In the first phase of this work, a number of energy efficient protocols have been studied. In this phase an energy efficient clustering scheme is developed modifying an existing clustering technique namely Low-Energy Adaptive Clustering Hierarchy (LEACH). Finally the performance of the present scheme is measured and compared with the LEACH and another existing scheme via MATLAB Simulation Tools. And the results clearly show that itâ€™s performed 17%-21 % better than existing protocolsÂ Â